Association between domains of quality of life and patients with klinefelter syndrome: a systematic review. - Mehmet,B; Gillard,S; Jayasena,CN; LLahana,S (European Journal of Endocrinology, 2022)
Klinefelter syndrome (KS) is the second-most prevalent chromosomal disorder in men, though late diagnosis is very common and 50-75% of men remain undiagnosed. Evidence suggests that men with KS have impaired Quality of Life (QoL) but research on how the diagnosis of KS is associated with different QoL domains and what factors influence patients' QoL is limited. This study aimed to provide a systematic review of the published evidence on factors that influence QoL in men with KS. DESIGN: Systematic review and meta-analysis with narrative synthesis. METHODS: Medline, Cochrane, Embase, Psychinfo, CINAHL, BASE and relevant publication reference lists were searched in January 2021. Eligible studies included RCTs, cohort studies, cross-sectional studies and epidemiology studies on KS and its effect on QoL and all domains of WHOQOL-100. Clinical studies with no date restriction published in English were included. RESULTS: Thematic analysis was completed on thirteen studies, with a meta-analysis of intelligence quotient (IQ) completed on seven studies. Twelve out of 13 studies suggested that KS negatively affected QoL outcomes and KS was associated with impairments in physical, psychological, level independence and social relationship domains of WHOQOL-100. Meta-analysis suggested men with KS have significantly lower full-scale Intelligence Quotient versus controls (P <0.00001). CONCLUSIONS: This is the first evidence synthesis of QoL in men with KS. Current evidence suggests that combined physical and psychological impairments affect men with KS who also experience impairments in relationships and independence in society. Further research is needed to identify factors that influence QoL in men with KS.